PENERAPAN CONTEXTUAL TEACHING LEARNING (CTL) DALAM PERKULIAHAN STRATEGI DAN METODE PEMBELAJARAN PAI - Zulfatmi Zulfatmi (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2018)
Course Lectures and Learning Methods The PAI leads students to understand and apply strategies and methods in the education and teaching of Islamic Religious Education very well in accordance with the spirit of PAI. If the lecturer talks or discusses which only has an impact on activating the analytical thinking aspect, and possibly up to the critical areas of the student, it can be ascertained that the creative and innovative thinking sphere of the students has not been better empowered, and makes learning less meaningful. To reinforce the students' learning experience requires more learning to give them the opportunity to think, do, try, and experience themselves, by linking the material to the context of their lives. This activity allows the critical thinking, creative and innovative thinking potential to be optimally empowered. Contextual Teaching Learning (CTL) or contextual learning is a learning model that can help lecturers relate between the material they are teaching and the real-world situations of the students and encourage them to make connections between their knowledge and application in the context of real life